Influence of the CapCut Application on the ICT Learning Performance - Syamsuddin , Nur; Tahir, Hijaz; Syamsunir, Syamsunir; Hasanuddin, Hasanuddin; Hermansyah, Sam (Research Horizon, 2023)
In today's digital age, the integration of technology into education has become paramount. CapCut, a versatile video editing application, has emerged as a valuable tool for educators. This study explores the multifaceted utility of CapCut in enhancing Information and Communication Technology (ICT) learning outcomes among Indonesian students. The purpose of this study is to investigate the impact of using the CapCut application on the learning outcomes of the seventh-grade students at State Islamic Junior High School (MTs Negeri) 2 Sidenreng Rappang. This research comprises a group of 38 students, where two significant variables are scrutinized: the independent variable, which pertains to the particular utilization of CapCut (X), and the dependent variable, which concerns the ultimate result of ICT learning in the seventh-grade class (Y). The techniques employed for data collection encompass observation, testing, and documentation.